Zika virus and the fetal-maternal interface: deciphering the mechanisms of placental infection and implications for pregnancy outcomes - Sam Chak Sum Wong; Joshua Fung; Pak-Ting Hau; Yanjie Guo; Philip C. N. Chiu; Hong Wa Yung; Gilman Kit Hang Siu; Franklin Wang-Ngai Chow; Cheuk-Lun Lee (Emerging Microbes and Infections, 2025)
Zika virus (ZIKV) is an emerging flavivirus primarily transmitted by Aedes mosquitoes. It has gained significant attention due to its potential teratogenic effects during pregnancy, particularly the increased risk of severe congenital outcomes such as microcephaly and fetal mortality. ZIKV's ability to breach the fetal-maternal interface and compromise placental function distinguishes it from other arboviruses. This mini-review explores how ZIKV targets key placental cells, including cytotrophoblasts, extravillous trophoblasts, syncytiotrophoblasts, and Hofbauer cells, to establish infection in the placenta. We first explore the molecular mechanisms of ZIKV replication, focusing on viral entry, replication strategies, and evasion of host immunity in trophoblasts. We then discuss how ZIKV infection triggers cellular stress responses, such as oxidative stress, endoplasmic reticulum stress, and inflammatory pathways, along with metabolic reprogramming. These processes ultimately lead to placental insufficiency and adverse pregnancy outcomes. Drawing on recent findings from trophoblast organoids and in vivo models, we highlight novel therapeutic opportunities, including vasoactive intestinal peptide, endoplasmic reticulum stress modulators, and immunomodulatory interventions that may protect pregnancy. Finally, we propose future directions for mitigating ZIKV’s impact on maternal-fetal health, emphasizing the need for comprehensive research into viral pathogenesis, advanced model systems, and vector control programmes to prevent this devastating infection.